Bio‐pharma in Iran: Escaping the middle‐income trap. (16th November 2022) - Babaee, Ali; Miremadi, Iman; Mashayekhi, Ali N.
Summary: Motivation: Neither state planning nor economic liberalization has allowed developing economies to escape from the middle‐income trap, owing mainly to institutional voids and hindering institutions. We need another explanation for development and the emergence of new institutions. Purpose: How have biopharmaceutical enterprises emerged in Iran, despite the obstacles faced? Can the collaborative agency of small groups of actors who know each other create new institutions and hence the conditions for biopharmaceutical firms to emerge? If so, who participates in such small groups, and how do they operate? Methods and approach: We interviewed 29 key participants and stakeholders in the Iranian bio‐pharma industry. We used grounded theory to identify key themes. Findings: Bio‐pharma emerged owing to the efforts of a small group who successfully worked together to master the technology, to overcome institutional obstacles and widespread scepticism within Iran, and thereby to create new firms manufacturing biopharmaceuticals. The group succeeded because it was morally committed to creating the industry; it proceeded pragmatically, experimenting and learning; and leadership was shared and collective. Policy implications: In this case, we see the inverse of a top‐down process where government acts as principal and firms act as agents. Instead, strategic collaboration across government, university and firms, in a process of trial and error, has been able to make great progress to overcome obstacles to technical innovation that seem daunting for a middle‐income country.